Comparative Evaluation of Nyctanthes arbor tristis and Alstonia scholaris Leaves Extracts in Freunds Complete Adjuvant Induced Arthritis in Rats - Goyal, Swapnil (International Journal of Pharmaceutical & Biological Archive, 2014)
Comparative Evaluation of Nyctanthes arbor tristis and Alstonia scholaris Leaves Extracts in Freunds Complete Adjuvant Induced Arthritis in Rats